Reformation Readings of the Apocalypse Geneva, Zurich, and Wittenberg - Backus, Irena (New York Oxford University Press, 2000)
In this study, Irene Backus examines the fate of the Apocalypse at the hands of early Protestants in three centers of the Reformation: Geneva, Zurich, and Wittenberg. To do so, Backus systematically investigates sources and methods of the most important
Keywords: Bible. -- Revelation -- Criticism, interpretation, etc. -- History -- 16th century. Bible -- Criticism, interpretation, etc. -- History -- 16th century. Bible. -- Revelation -- Criticism, interpretation, etc. Reformation. Bible. -- New Testament. -- Apoca